(untitled) (Revista Educação, Artes e Inclusão, 2022)
This article aims to address the role of the painter Maria Amélia D’Assumpção, in the context of Paraná art at the beginning of the 20th century, highlighting aspects of her formation, trajectory, creation and insertion in the artistic circle of the city of Curitiba, capital of the state. We started from an interdisciplinary perspective, dialoguing with the field of history and the arts, to problematize the socio-cultural context, as well as the gender relations that implied the performance and recognition of women artists in the studied period, since not all social spaces were open to them. For the analysis of some of his works - portraits and still lifes - the methodological procedures of Erwin Panofsky’s iconographic/iconological analysis, to understand his social representations, artistic influences and meanings present in the construction of his images. In this way, her role is noticeable both in the profession of artist and in the teacher of art education who integrated life and history.